Climate Change Engagement: Youth Perspectives and Pathways to Climate Action (International Journal of Environmental Sciences, 2025)
This mixed-methods study investigates the factors influencing climate change engagement among secondary school students (N = 45). The research examines the interplay of awareness, perception, beliefs, willingness, and intention by integrating quantitative surveys and qualitative focus group discussions. Quantitative findings reveal that while willingness, beliefs, and perception significantly correlate with intention (p < .001), awareness does not. Qualitative data elucidate the diverse sources of climate change information for students and their nuanced understanding of climate change impacts. The study concludes that interventions should prioritize fostering willingness, beliefs, and perceptions to enhance youth engagement in climate action, moving beyond a sole focus on awareness.